2022
DOI: 10.1039/d2qo00396a
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective 1,2-carbosulfenylation of unactivated alkenesviadirected nickel catalysis

Abstract: A bidentate directing group-assisted Ni-catalyzed three component 1,2-carbosulfenylation of unactivated alkenes with aryl/alkenylboronic acids and disulfide electrophiles is reported. The reaction affords the desired products with high levels of chemo-...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…12 The relative stereochemistry was established by X-ray crystallographic analysis, and the diastereoselectivity might arise from steric hindrance. 8 a ,13 In addition, the coupling of 3a with 4-( tert -butyl)benzenethiol afforded α,α-difluoroalkylthioether 5b in 86% yield with >20 : 1 dr. 14 When 3a was treated with imidazole and NaH, it could undergo a nucleophilic vinylic substitution reaction (S N V) to form 5c in 87% yield. 15 Unexpected intramolecular C–F activation/cyclization was observed, providing fluoro-containing 2,3-dihydropyrrole 5d .…”
Section: Resultsmentioning
confidence: 99%
“…12 The relative stereochemistry was established by X-ray crystallographic analysis, and the diastereoselectivity might arise from steric hindrance. 8 a ,13 In addition, the coupling of 3a with 4-( tert -butyl)benzenethiol afforded α,α-difluoroalkylthioether 5b in 86% yield with >20 : 1 dr. 14 When 3a was treated with imidazole and NaH, it could undergo a nucleophilic vinylic substitution reaction (S N V) to form 5c in 87% yield. 15 Unexpected intramolecular C–F activation/cyclization was observed, providing fluoro-containing 2,3-dihydropyrrole 5d .…”
Section: Resultsmentioning
confidence: 99%
“…Besides sulfonamide sulfenylating agents, the Wang group 73 found that simple aryl disulfides ( 250 , Scheme 42) were also competent to oxidize Ni( i ) ( 254 ) to the sulfenyl Ni( iii ) intermediate ( 255 ) and furnish the 1,2-arylsulfenylation products ( 251 ) chemo- and regioselectively from unactivated alkenes ( 248 ) and arylboronic acids ( 249 ). In this process, the assistance of the intramolecular bidentate coordination of PA auxiliary (picolinamide) was proposed to stabilize the active nickel intermediates.…”
Section: Transition-metal Catalyzed Carbosulfenylationmentioning
confidence: 99%
“…To the best of our knowledge, very few methods for carbosulfenylation of alkenes have been reported with transition metal catalysts (Scheme 1c). 10 Our main aim was to develop an environmentally benign cost-effective MCR approach for carbothio di-functionalization of alkenes under redox-neutral conditions. Here, we report a method for carbo(sp 3 )-thioaryl/alkylation of activated alkenes via C(sp 3 )–H bond functionalization, where we have used an easy-to-prepare and -handle N -(aryl/alkyl-thio)phthalimide as an electrophilic thiolating reagent and Ph-Mes-Acr + BF 4 − as a photocatalyst under visible-light irradiation (Scheme 1d).…”
Section: Introductionmentioning
confidence: 99%